2020
DOI: 10.1177/0098628320979895
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Handwritten Notes: A Failure to Find State-Dependent Effects When Using a Laptop to Take Notes and Complete a Quiz

Abstract: Background: Many students use laptops in the classroom to take notes; however, even when laptops are used for the sole purpose of taking notes they can negatively impact academic performance. Objective: The current study examined state-dependent effects, and the potential for a match in note taking and quiz taking methods to improve quiz performance. Method: Participants were placed into a congruent (take notes by hand and complete the quiz by hand or take notes using a laptop and complete an online quiz) or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Journal of Learning Development in Higher Education, Issue 24: September 2022 11 example, P11 spoke of liking being able to scribble notes over print texts, and touch and interact with them, and P16 highlighted his lack of engagement with notes when typing in contrast to writing. Similar to the experiences of our students, research on note-taking has found that students encode memory more efficiently when handwriting notes as opposed to typing (Crumb et al, 2022).…”
Section: Reading and Note-takingsupporting
confidence: 70%
“…Journal of Learning Development in Higher Education, Issue 24: September 2022 11 example, P11 spoke of liking being able to scribble notes over print texts, and touch and interact with them, and P16 highlighted his lack of engagement with notes when typing in contrast to writing. Similar to the experiences of our students, research on note-taking has found that students encode memory more efficiently when handwriting notes as opposed to typing (Crumb et al, 2022).…”
Section: Reading and Note-takingsupporting
confidence: 70%